NON-STANDARD TESTS IN MOTHER TONGUE EDUCATION AND IMPROVEMENT OF METHODOLOGY OF THEIR USE - Murodova Ruxsora Ismatilla qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the effectiveness of tests, assignments, and educational games in developing speaking skills in the native language methodology.